Distribution of the As, Cu, Mn, Pb, Zn in the Verbascum euphraticum L. Root and Growing on Stream Sediments in the Geli Dere (Baskil-Elazığ) Vicinity - Kara, Hatice; Kalender, Leyla (Fırat University, 2015)
Biochemical prospection is a study carried out with data of plant chemistry and applied intensively and successfully throughout the world. This study includes As, Cu, Mn, Pb and Zn content of the upper level sand bar along wide and shallow Baskil-Geli Dere drainage system which is included within the class of braided river and Verbascum euphraticum L. growing on its. In this study, As, Cu, Mn, Pb and Zn contents of stream sedimentand Verbascum euphraticum L. (local name: mullein) roots were compared and investigated bioindicator and bioaccumulator features of Verbascum euphraticum L. roots, As 22.5-176.9 mg kg?1, Cu 42.46148.73 mg kg?1, Mn 736-1093 mg kg?1, Pb 29.34-106.57 mg kg?1 and Zn 91.1-303.2 mg kg?1 contents were determined in stream sediments along the Geli Dere, and As 2.2-22.2 mg kg?1, Cu 53.59-116.95 mg kg?1, Mn 62-344 mg kg?1, Pb 2.43-45.22 mg kg?1, Zn 64.7-158 mg kg?1 in Verbascum euphraticum L. roots at the same sites. The calculated bioaccumulator factor values of As, Cu, Mn, Pb and Zn are range from 0.09 to 0.7; 0.49 to 2.24; 0.09 to 0.34; 0.08- to 0.95; 0.34 to 1.73, respectively. As a result, it can be said that Verbascum euphraticum L. roots for Cu and Zn may be used bioindicator and bioaccumulator plant and successfully for biogeochemical prospecting

Bitki kimyası verilerden yararlanılarak yapılan prospeksiyon çalışması olan biyojeokimyasal prospeksiyon dünyada başarılı bir şekilde uygulanmaktadır. Bu çalışmada, örgülü nehir sınıfına giren geniş ve eğimi oldukça düşük Baskil-Geli Dere drenaj sistemi boyunca kum barları üzerinde yetişen Verbascum euphraticum L. (yerel adı: sığırkuyruğu) kökleri ve dere sedimenti örneklerinde As, Cu, Mn, Pb ve Zn değerleri karşılaştırılarak Verbascum euphraticum L.’nin biyojeokimyasal prospeksiyon çalışmalarında biyoindikatör veya biyoakümülatör olma özelliği araştırılmıştır. Geli Dere boyunca alınan dere sedimentlerinde As 22,5-176,9 mg kg?1, Cu 42,46-148,73 mg kg?1, Mn 736-1093 mg kg?1, Pb 29,34-106,57 mg kg?1 ve Zn 91,1-303,2 mg kg?1, Verbascum euphraticum L. kökünde ise As 2,2-22,2 mg kg?1, Cu 53,59-116,95 mg kg?1, Mn 62-344 mg kg?1 , Pb2,43-45,22 mg kg?1 ve Zn 64,7-158 mg kg?1 değerler arasındadır. Biyoakümülatör faktör değerleri As 0,09-0,7, Cu 0,49-2,24, Mn 0,09-0,34, Pb 0,08-0,95 ve Zn 0,34-1,73’tür. Bu veriler sonucunda V. euphraticum kökünün Cu ve Zn için biyoindikatör ve biyoakümülatör bitki olduğu ve biyojeokimyasal prospeksiyonda başarılı bir şekilde kullanılabileceği söylenebilir.
Geli Dere (Baskil-Elazığ) Çevresindeki Verbascum euphraticum L. Köklerinde ve Üzerinde Yetiştiği Dere Sedimentindeki As, Cu, Mn, Pb ve Zn’nun Dağılımı
Keywords: Engineering; Mühendislik